FORM THE MOTIVATION OF CREATIVE ACTIVITY IN STUDENTS PSYCHOLOGICAL CHARACTERISTICS (Academia Science Repository, 2023)
In this article, students' creative activity, motivation, understanding of activity, psychological characteristics, general concepts of the motivation process, about the processes of the educational activity, the skill set, the motivational reason for activity. Opinions are given about the analysis of the work performed according to the image of the desired goal, i.e., the result achieved by the performance of the activity.